Räumliche Bevölkerungsentwicklung in Griechenland und Rumänien. Ein Vergleich - Heller, Wilfried (ERDKUNDE, 1975)
On the whole the socio-economic situation has decisively improved over the last decades in both countries. Regional disparities, however, have not disappeared. In Greece they have even become more acute because of the uncontrolled concentration of economic activity in the Thessaloniki region, more particularly in Greater Athens. Planning authorities have not yet had the means to implement their concept of economic development, which has a better grase of the economic aspects of the entire population and is therefore more balanced concerning spatial aspects. State planning authorities in Romania however have those means. In spite of this, regional disparities continue even there. A further development of spatial disparity can still be observed, but not as noticeably as before. These facts of population growth have been demon strated by a statistical analysis. For this purpose it was necessary to not only consider the statistical average of the states and governing regions but also to further differentiate between the communities of those selected areas. Drawing correlations has shown that in the planned economy of Romania the factors of settlement size and distance from a community to the next large city have indeed influenced population growth. However this was true to a lesser degree than in Greece.